Rumen microbiota of indigenous and introduced ruminants and their adaptation to the Qinghai–Tibetan plateau - Li, Bin; Jia, Gaobin; Wen, Dongxu; Zhao, Xiuxin; Zhang, Junxing; Xu, Qing; Zhao, Xialing; Jiang, Nan; Liu, Zhenjiang; Wang, Yachun (Frontiers in Microbiology, 2022)
The grassland in the Qinghai Tibetan plateau provide habitat for many indigenous and introduced ruminants which perform important ecological functions that impact the whole Qinghai Tibetan plateau ecosystem. These indigenous Tibetan ruminants have evolved several adaptive traits to withstand the severe environmental conditions, especially cold, low oxygen partial pressure, high altitude, strong UV radiation, and poor forage availability on the alpine rangelands. Despite the challenges to husbandry associated with the need for enhanced adaptation, several domesticated ruminants have also been successfully introduced to the alpine pasture regions to survive in the harsh environment. For ruminants, these challenging conditions affect not only the host, but also their commensal microbiota, especially the diversity and composition of the rumen microbiota; multiple studies have described tripartite interactions among host-environment-rumen microbiota. Thus, there are significant benefits to understanding the role of rumen microbiota in the indigenous and introduced ruminants of the Qinghai Tibetan plateau, which has co-evolved with the host to ensure the availability of specific metabolic functions required for host survival, health, growth, and development. In this report, we systemically reviewed the dynamics of rumen microbiota in both indigenous and introduced ruminants (including gut microbiota of wild ruminants) as well as their structure, functions and interactions with changing environmental conditions, especially low food availability, that enable survival at high altitudes. We summarized that three predominant driving factors including increased VFA production, enhanced fiber degradation, and lower methane production as indicators of higher efficiency energy harvest and nutrient utilization by microbiota that can sustain the host during nutrient deficit. These cumulative studies suggested alteration of rumen microbiota structure and functional taxa with genes that encode cellulolytic enzymes to potentially enhance nutrient and energy harvesting in response to low quality and quantity forage and cold environment, Future progress towards understanding ruminant adaptation to high altitudes will require the integration of phenotypic data with multi-omics analyses to identify host-microbiota co-evolutionary adaptations enabling survival on the Qinghai Tibetan plateau.